Peningkatan Pemahaman Fiqh Kewanitaan melalui kajian kitab Kifayatul Mubtadiin pada Ibu rumah tangga di Desa Simpang Purwakarta - Ahmad Fajar; Dede Mariah (Penerbit Widina, Widina Media Utama, 2022)
Improved Understanding of Fiqh Femininity fiqh womanhood in village Simpang Through the Study of the Book Kifayatul Mubtadiin It can be a routine study local people improving understanding housewife the science of fiqh about womanhood. This routine study is carried out three times in one week for one month These are the housewives in Simpang village. purpose of devotion improve the understanding of the fiqh of womanhood for housewives. The method used is the lecture method. The book fiqh he studied was Jifayatul Mubtadiin. With this activity, The housewives in Simpang village Become aware and know how to procedure Good and correct worship in accordance with Islamic law.